2021
DOI: 10.1111/bjet.13102
|View full text |Cite
|
Sign up to set email alerts
|

Students’ experience of online learning during the COVID‐19 pandemic: A province‐wide survey study

Abstract: Online learning is currently adopted by educational institutions worldwide to provide students with ongoing education during the COVID‐19 pandemic. Even though online learning research has been advancing in uncovering student experiences in various settings (i.e., tertiary, adult, and professional education), very little progress has been achieved in understanding the experience of the K‐12 student population, especially when narrowed down to different school‐year segments (i.e., primary and secondary school s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
136
0
13

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(156 citation statements)
references
References 46 publications
7
136
0
13
Order By: Relevance
“…These findings are consistent with some previous studies. For example, Yan et al (2021) reported similar deficiencies caused by homebased learning (e.g., the eyestrain caused by staring at screens for a long time, poor course design, poor experience with online learning platforms). Kim also claimed that children generally spent less time on physical activities and gained weight during school closure (Kim et al, 2021).…”
Section: Key Factors Influencing Parents' Willingness To Let Their Children Return To Schoolmentioning
confidence: 99%
“…These findings are consistent with some previous studies. For example, Yan et al (2021) reported similar deficiencies caused by homebased learning (e.g., the eyestrain caused by staring at screens for a long time, poor course design, poor experience with online learning platforms). Kim also claimed that children generally spent less time on physical activities and gained weight during school closure (Kim et al, 2021).…”
Section: Key Factors Influencing Parents' Willingness To Let Their Children Return To Schoolmentioning
confidence: 99%
“…Keadaan darurat saat ini mengharuskan sistem pembelajaran diganti dengan pembelajaran online agar proses pembelajaran tetap berjalan. Hal ini jelas mengubah pola pembelajaran melalui media digital jarak jauh salah satunya menggunakan media interaktif yang tentunya tidak mengorbankan kualitas pendidikan sehingga memberikan efek positif terhadap proses pembelajaran yang memberikan kebebasan bagi siswa (Owston & York, 2018;Smith & Hill, 2019;Van Lancker & Parolin, 2020;Yan et al, 2021).…”
Section: Pendahuluanunclassified
“…By this meaning tudents' online learning experience during the COVID-19 pandemic has identified several major concerns, challenges, services. (Yan, L. et al 2021) These services include monitoring and evaluating students, and providing grades, as well as the additional administrative actions required for educational processes in higher education. With the pandemic spreading, many countries have shut down all the educational institutions, shifting to online learning platforms to keep the academic processes going.…”
Section: Introductionmentioning
confidence: 99%